1995
DOI: 10.1071/rd9951185
|View full text |Cite
|
Sign up to set email alerts
|

Development of the gonads in the triploid (ZZW and ZZZ) fowl, Gallus domesticus, and comparison with normal diploid males (ZZ) and females (ZW)

Abstract: Gonadal development in fowls aged from 1 day to more than 4.5 years was studied in 63 ZZW and 16 ZZZ triploid crossbreds and compared with normal diploid males (ZZ) and females (ZW). In the ZZW fowl, the right gonad developed into a testis (although this occurred earlier in the ZZ genotype), and a structurally-abnormal excurrent duct system containing some malformed spermatids and spermatozoa was associated with the gonad of young adults. The left gonad was an ovotestes at hatching and no excurrent ducts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 0 publications
1
50
2
Order By: Relevance
“…They were phenotypically female, but the ovarian component of the ovotestis degenerated, and birds became male at sexual maturity. (9) The observations made on these triploid chickens suggest that the W chromosome carries a female determinant, which can be antagonised by the dosage of a Z-linked male-determinant. Regression of ovarian tissue in ZZW triploid chickens implies that the putative W-linked female determinant is not dominant.…”
Section: Z Dosage or Dominant W?mentioning
confidence: 97%
“…They were phenotypically female, but the ovarian component of the ovotestis degenerated, and birds became male at sexual maturity. (9) The observations made on these triploid chickens suggest that the W chromosome carries a female determinant, which can be antagonised by the dosage of a Z-linked male-determinant. Regression of ovarian tissue in ZZW triploid chickens implies that the putative W-linked female determinant is not dominant.…”
Section: Z Dosage or Dominant W?mentioning
confidence: 97%
“…Triploid chickens with an ZWW genotype are not viable, whereas triploid ZZZ chickens develop a male phenotype but produce only abnormal sperm. Triploid ZZW chickens initially develop female phenotypes but before sexual maturity they develop male phenotypes [8]. Importantly, these intersexual chickens fail to produce viable gametes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Triploid ZZW chickens initially develop female phenotypes but before sexual maturity they develop male phenotypes [8]. Importantly, these intersexual chickens fail to produce viable gametes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas 3A:ZZZ birds developed as fairly normal males, 3A:ZZW birds developed as intersexes. At hatching, the 3A:ZZW birds had a right testis and a transient left 'ovotestis' with both ovarian and testicular structures (Lin et al 1995). Phenotypically female at hatching, the birds eventually lost the ovarian component of the left gonad and they became male at sexual maturity.…”
Section: The Molecular Mechanism Of Avian Sex Determinationmentioning
confidence: 99%
“…However, such sex chromosome aneuploids have not been definitively documented in birds (Clinton 1998) and it has been suggested that such genotypes may be lethal to embryos (Marshall Graves 2003). Marney Thorne and Bruce Sheldon, working at the CSIRO Animal Production Division, described a line of triploid Chickens, with the genome present in triplicate (3A rather than 2A), including the sex chromosomes (Lin et al 1995;Thorne 1995;Thorne et al 1997). Whereas 3A:ZZZ birds developed as fairly normal males, 3A:ZZW birds developed as intersexes.…”
Section: The Molecular Mechanism Of Avian Sex Determinationmentioning
confidence: 99%